Effects of different structures and allocations on fluid flow and heat transfer performance in 3D-IC integrated micro-channel interlayer cooling. (December 2015) - Xia, G.D.; Ma, D.D.; Wang, W.; Zhai, Y.L.
Highlights: Interlayer micro-channel cooling is a promising solution for high heat flux 3D-IC. The smaller pitch enhanced heat transfer, but enlarged pressure drops dramatically. The smaller length enhanced heat transfer and decreased pressure drops. The surface enhancement micro-channel TRC and FRC enhanced heat transfer. 3D-IC with FRC-L5-P0.2 has better thermal performance and lowest pumping power. Abstract: 3D-IC is getting increasingly attractive, as it improves speed and frequency and reduces power consumption, noise and latency. However, three-dimension (3D) integration technology brings a new serious challenge to chip thermal management with the power density increased exponentially. Interlayer micro-channel liquid cooling is a promising and scalable solution for high heat flux removal in 3D-IC. The effects of geometric parameters on fluid flow and heat transfer characteristics in interlayer micro-channel cooling for 3D-IC with triangular reentrant cavities (TRC) and fan-shaped reentrant cavities (FRC) are numerically investigated. 3D-IC with TRC and FRC for pitch = 0.1/0.2 mm and height = 0.2 mm are analyzed and compared with rectangular micro-channel (RMC) for 1 cm 2 heat areas. Results show that the heat rate and pressure drop distributions of each layer for length = 5 mm and pitch = 0.2 mm are more uniform. The micro-channels of pitch = 0.1 mm have better heat transfer performance, simultaneously cause the pressure drop and pumping power increasing sharply, which are undesirable and uneconomical for 3D-IC. For smaller Re, the micro-channels with surface enhancement structures TRC and FRC deteriorate heat transfer. While at the larger Re, heat transfer is enhanced, which can be attributed to heat transfer area increased, boundary layer thinned, boundary layer interrupted and chaotic advection by generating vortices. The 3D-IC with FRC-L5-P0.2 has better heat transfer performance and lowest pumping power, which is more suitable and economical for 3D-IC inter-layer cooling. For channel length of 10 mm, the fluid temperature is higher in the last 5 mm, which deteriorates heat transfer effect, simultaneously the longer length leads to pumping power and flow resistance enlarged. Besides, 3D-IC with FRC decreases the laminar stagnation zones and improves the heat transfer performance, due to owning bigger included angle of the expansion and constriction walls in channel.